Optimum Reverberation Time of Classrooms for Incomplete Hearing People Using Speech Intelligibility Tests - Chan-Hoon Haan (Theory and Applications of Engineering Research Vol. 7, 2024)
Because speech recognition performance is significantly lower at the age of nine or younger, and age over 65. The acoustic performance standards of classrooms for these people, incomplete hearing people, should be investigated separately. This study derives the appropriate reverberation time of classrooms for both lower-grade elementary school pupils and elderly in Korea. A virtual sound field was created by computer modeling using normalized classrooms of Korean elementary schools. A total of five classrooms with reverberation times from 0.6 s to 1.2 s were produced by varying the sound absorption coefficient of the ceiling. Auralized sounds were produced by synthesizing anechoic sounds of words in a virtual sound field. Speech intelligibility tests were undertaken with 20 young pupils and 50 elderly people. As a result, it was concluded that the reverberation time suitable for lower-grade classrooms of elementary schools should be below 0.6 s because test scores were significantly lower when RT was longer than this value. Also reverberation time below 0.8s was suggested for the learning space for elderly people.